A efetividade do direito a partir do princípio holonômico: uma ideia de justiça integrativa - Licarião Neto, Moaci (2024)
The present work follows the methodological path of bibliographic research, having as an investigative intention the effectiveness of Law, observed from the holonomic principle as an instrument capable of subsidizing the idea of an Integrative Justice. Due to the relevance of the approach and the importance of the arguments constructed, the research takes as its starting point the reflection and analysis of the ideals of justice as equity and the notion of distributive justice defended by John Rwals and Ronald Dworkin, respectively. From the analysis of the main elements of the thesis defended by Rwals and Dworkin, the research expands the understanding of the traditional elements of the respective theories of justice, adopting as a theoretical reference the foundations of the Theory of Complexity proposed by Edgar Morin and the Idea of Justice defended by Amartya Sen. Through the dialogue between these theories, it is possible to establish minimum requirements/elements/criteria for the construction of the idea of an Integral Justice. From the analysis it can be evidenced that the proposal of a reflection on the idea of Integrative Justice from the perspective of complexity seems to be an appropriate measure in the search for ways that aim to bring greater effectiveness to the Law. From the developments resulting from the initial investigation, the holonomic principle is observed as a complex and multidimensional source of values and guidelines that instrumentalize and guide the idea of Integrative Justice for the consolidation of rights. It is noteworthy that the analysis carried out addresses the issue of the effectiveness of the Law and the reflections on the idea of justice, through the symptomatic manifestation of the injustices and ineffectiveness of the law, materialized through the problem of vulnerabilities. In this way, it seeks to evidence elements that can confirm the hypotheses raised, in order to establish minimum criteria of identification and pertinence to the scope of the research, aiming at the effectiveness of the Law observed from the holonomic principle as a possible path that should lead to the construction of an idea of integrative justice